2020
DOI: 10.3390/ma13245798
|View full text |Cite
|
Sign up to set email alerts
|

Spinel-Type (FeCoCrMnZn)3O4 High-Entropy Oxide: Facile Preparation and Supercapacitor Performance

Abstract: High-entropy oxides (HEOs) have attracted more and more attention because of their unique structures and potential applications. In this work, (FeCoCrMnZn)3O4 HEO powders were synthesized via a facile solid-state reaction route. The confirmation of phase composition, the observation of microstructure, and the analysis of crystal structure, distribution of elements, and valences of elements were conducted by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…Concerning the spectrum of Mn 2p in Fig. 9(f), it can be readily observed that the main peaks at 640.9 eV (Mn 2p 3/2 ) and 652.6 eV (Mn 2p 1/2 ) are indexed to Mn 2+ species, and the peaks at 642.8 eV (Mn 2p 3/2 ) and 654.1 eV (Mn 2p 1/2 ) are related to Mn 3+ species [52]. The spectrum of Ni 2p shown in Fig.…”
Section: Electrochemical Properties Of Hepo Electrodesmentioning
confidence: 98%
“…Concerning the spectrum of Mn 2p in Fig. 9(f), it can be readily observed that the main peaks at 640.9 eV (Mn 2p 3/2 ) and 652.6 eV (Mn 2p 1/2 ) are indexed to Mn 2+ species, and the peaks at 642.8 eV (Mn 2p 3/2 ) and 654.1 eV (Mn 2p 1/2 ) are related to Mn 3+ species [52]. The spectrum of Ni 2p shown in Fig.…”
Section: Electrochemical Properties Of Hepo Electrodesmentioning
confidence: 98%
“…In all samples, the diffraction peaks correspond to the reflections of fcc spinel structure, belonging to Fd% 3m space group (JCPDS no. 22-1084) 51,52,56,61,[71][72][73][74][75][76] No additional peaks attributable to secondary phases are detected, indicating that a single-phase is formed for any composition, namely (Cr where k (0.9) is the shape factor, l is the wavelength of X-ray radiation, b is the FWHM in radians and y is the Bragg's angle. 77 The obtained values increase in the order CoZn (83.7 nm) o CoNi (97.0 nm) o NiZn (98.5 nm), respectively.…”
Section: Crystalline Phase Of the Oxidementioning
confidence: 99%
“…Because Kong et al did not carry out high-temperature oxidation and used the area-specific capacitance scheme, the electrochemistry of the two materials was quite different. Compared with the HEOs with the same composition prepared by a solid-state reaction, this experiment has a similar potential window, rate, and cycle stability. However, the specific surface area of the material prepared by the dealloying scheme is enlarged to some extent; thus, the specific capacitance is improved.…”
Section: Resultsmentioning
confidence: 99%